Approximate controllability of infinite dimensional systems of the n-th order - Respondek, Jerzy Stefan (Zielona Góra: Uniwersytet Zielonogórski)
The objective of the article is to obtain general conditions for several types of controllability at once for an abstract differential equation of arbitrary order, instead of conditions for a fixed order equation. This innovative approach was possible owing to analyzing the n-th order linear system in the Frobenius form which generates a Jordan transition matrix of the Vandermonde form.
Keywords: inverse Vandermonde matrix; basic symmetrical polynomials; distributed parameter system; linear operators; controllability